Pemberdayaan Siswa dalam Peningkatan Pengetahuan Mengenai Teknik Menyikat Gigi yang Benar Serta Penggunaan Tongue Scraper - Ernie Thioritz; Badai Septa Wahyudadi; Jumriani Jumriani; Ira Liasari; Asridiana Asridiana; R Ardian Priyambodo; Asriawal Asriawal (Abdimas Mandalika, 2022)
Abstract:  This community service activity was carried out with the aim of empowering SMP YP PGRI Disamakan Makassar students in increasing knowledge and skills on how to brush their teeth properly and use a tongue scraper. Activities are carried out in several stages. The first stage was a pre-test in the form of a questionnaire to 39 students and asked students to do a demonstration of brushing their teeth before counseling. In the second stage, participants were given counseling and demonstrations on how to maintain oral hygiene by brushing their teeth and using a tongue scraper. In the third stage, participants were given a post test and asked to demonstrate again after the counseling. Based on the evaluation of the activities, there has been an increase in the knowledge and skills of students after counseling and demonstrations on how to maintain dental health by brushing teeth and using a tongue scraper correctly. Students who have good knowledge about how to maintain oral health increased by 64.1%. The number of students who were able to brush their teeth properly increased by 65.67%. Meanwhile, students who were able to use a tongue scraper correctly increased by 69.23%. Therefore, outreach activities need to be held regularly to get optimal results. Abstrak: Kegiatan pengabdian masyarakat ini dilaksanakan dengan tujuan untuk memberdayakan siswa SMP YP PGRI Disamakan Makassar dalam peningkatan pengetahuan dan keterampilan mengenai cara menyikat gigi yang benar serta menggunakan tongue scraper.  Kegiatan dilakukan melalui beberapa tahap. Tahap pertama adalah pre test berupa kuesioner kepada 39 orang siswa dan meminta siswa untuk melakukan demonstrasi menyikat gigi sebelum penyuluhan. Pada tahap kedua peserta diberikan penyuluhan dan demonstrasi tentang cara pemeliharaan kebersihan gigi dan mulut dengan cara menyikat gigi dan  menggunakan tongue scraper. Tahap ketiga peserta diberikan post test dan diminta melakukan demonstrasi kembali setelah penyuluhan. Berdasarkan evaluasi kegiatan, telah terjadi peningkatan pengetahuan dan keterampilan siswa-siswi setelah dilakukan penyuluhan dan demonstrasi mengenai cara pemeliharaan kesehatan gigi dengan cara menyikat gigi dan penggunaan tongue scraper yang benar. Siswa yang memiliki pengetahuan baik mengenai cara pemeliharaan kesehatan gigi dan mulut meningkat sebanyak 64,1%. Jumlah siswa yang mampu menyikat gigi yang benar meningkat sebesar 65,67%.  Sedangkan siswa yang mampu menggunakan tongue scraper dengan benar meningkat sebesar 69,23%. Oleh sebab itu kegiatan penyuluhan perlu diadakan secara berkala untuk mendapatkan hasil yang optimal.